PEMAHAMAN MANAJEMEN DALAM KELANCARAN PROSES KERJA BIDANG INDUSTRI PERUSAHAAN PASTA GIGI - Ahmad Sulthan Hidayatullah; Zsa Zsa Izazi (PUTRA JAWA PUBLISHER, 2024)
This Entrepreneurship Temporary Work Program provides practical experience for students by enhancing their knowledge, skills, motivation, and attitudes in an industrial setting. The program's primary goal is to instill entrepreneurial values and prepare students for the workforce after graduation. It involves a partnership between PT MADUSARI MAS Industry and PT UNILEVER, focusing on the production of toothpaste. The program includes both discussions and hands-on practice, allowing students to gain direct insight into the manufacturing process. The research focuses on product development, particularly the commercial stage, using qualitative methods, such as interviews with Pepsodent toothpaste users. Data from observations and interviews are compared through a triangulation method, involving categorization and theoretical analysis of product development, innovation, and consumer purchasing decisions. The results indicate that Pepsodent continuously innovates by expanding its product line to include mouthwash and toothbrushes, which impacts consumer needs and preferences.